Aksesbilitas Disabilitas Untuk Mewujudkan Pendidikan Yang Inklusif Di Lingkungan Pendidikan Tinggi - Muhammad Sulaeman; Hastin Trustisari (JURNAL ILMIAH NUSANTARA, 2024)
Education is a basic right of every individual, including people with disabilities. However, the accessibility of students with disabilities to higher education is still a problem. Some of them are the lack of infrastructure, supporting facilities, and appropriate curriculum. This article reviews the literature on how higher education is accessible to people with disabilities, identifies key challenges, and looks at ways to improve inclusion. This method uses literature research from academic sources. The results show that the main problems include the accessibility of facilities and the management and human resources of universities. Conclusion Universities must improve lecturer training, change the curriculum, and improve campus infrastructure to achieve this. It is hoped that the implementation of these strategies will result in a more inclusive and equitable education.